(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This research focuses on the debates, conflicts and proposals that generated around the proliferation of public clocks in México City between the years 1882 and 1922. Despite the proliferation of these machines, the possibilities of citizens to know the exact time was complicated by a number of problems detailed in the text. Facing these difficulties, scientist, journalists and public officials reacted by asking the unification of time, that is, the creation of a political and social conven- tion that would establish a single time for all the Mexican capital. The objective of this work is to establish the ambiguities and intricacies of this process of time standardization, due both to state as to civil society interests, and that, at the same time, involved aspects of positivist modernization while appealing to traditional elements. Demographic and spatial constitution of México City has been a topic addressed by historians, however, this research attempts to look at the construc- tion of a temporary experience in the city, which so far has not been explored.